ANALISIS PELAKSANAAN INOVASI PELAYANAN PUBLIK PADAKANTOR PERTANAHAN KOTA SEMARANG (Studi Kasus Pelayanan Mandiri Akta Tanah) - Sehsa Cantika; Dewi Rostyaningsih; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Community demands will the establishment of the government clean, accountable and transparent, encourage the government to start the amendments to penyusunannya in order to realize good governance ( good governance ). Public services in indonesia covering some field one of them land.As the lead government agency that are responsible for land, the land office the city of semarang has an important role in the delivery of to the community optimally.The land office the city of semarang in order to solve problems services happened, do innovation and breakthrough valor with formulate one form of innovation service.Program innovation service referred to the online services based application web commonly called “PERMATA” by the community. This study was conducted with the land office semarang city as agencies which implement innovation PERMATA.This research based on the researchers still several problems, which is there are some time / connection network server parent (data center) in the maintenance or error which is certainly will have an impact the stoppage of online service.In addition of KKP about trafic web disturbed because the operator that irresponsible. Based on the research, PERMATA deliver more values particularly the increase of performance and credibility for Semarang City land office.On the other hand PERMATA having complexity separate demand a training employees in increasing ability to be able to address issues concerning technology. Innovation occurring in the Semarang City land office, supported by several factors internal and external organization that is vision and strategy, human resources, culture organization, the state and government policy, and competition.